Core Competencies for Training Conservation Paleobiology Students in a Wicked World - Kelley, Patricia H.; Dietl, Gregory P. (Frontiers in Ecology and Evolution, 2022)
Despite the promise conservation paleobiology holds for using geohistorical data and insights to solve conservation problems, training in the field typically does not equip students to be competent environmental problem solvers. The intention of this perspective piece is to start a conversation about how we might train conservation paleobiology students better, focusing on the competencies needed to promote deep engagement with “wicked” conservation problems that are difficult to solve. Ongoing conversations regarding design of academic programs in sustainability, a field allied with conservation science, can inform our discussion. The sustainability literature has defined an interrelated set of “core competencies” that go beyond general academic competencies to enable real-world sustainability problem solving: systems thinking, temporal thinking, normative thinking, strategic thinking, and interpersonal competence. Conservation paleobiology is usually taught within geology programs, where students are exposed to systems thinking and temporal thinking. However, the remaining competencies typically are absent or insufficiently developed. To infuse these competencies into conservation paleobiology curricula, we recommend: 1) enhancing connections with sustainability programs and encouraging a more cross-disciplinary approach to training; 2) developing a “menu” of concepts and methodologies for each competence from which to choose; and 3) recognizing that different skills are appropriate at different levels of education and experience. The proposed competency-based framework serves as a shared reference that can be used to develop pedagogies to better prepare conservation paleobiology students to navigate the wicked conservation challenges of our time.